(untitled) (Nuntius Antiquus, 2013)
The twenty-two verses that make up Chapter 5 of Satyricon describe the guidelines of the formation of perfectus orator, as defined by Cato, Tacitus and Quintilian. However, the function of the poem in the assembly of this Latin novel is to accentuate the gap between educational theory during the early empire and the practice of an effective teaching of oratory – a practice deemed decadent since the final years of the republic. The poem, therefore, satirizes the educational processes at the time, serving as an object of sarcasm to the readers of ancient Rome.